FT IR EDXRF and gamma Isotopic Analyses of Ashes from Coal Fired Power Plants of Turkey - Varinlioğlu, Ahmet; Köse, Abdullah; Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Taylor and Francis Online, 1996)
Nine ash samples collected from five coal fired power plants of Turkey have been analysed by FT-IR, EDXRF and γ -isotopic analyses methods. IR spectroscopy together with mineralogical analysis is found to be a useful method for investigating the inorganic chemical composition of the ashes which is an inherently variable material due to differences in the inorganic chemical composition of the source coal and in ash collection. Gamma-isotopic analysis indicated that all samples contained Ra-226, U-238 and Th-232. On the other hand Cs-137 (16.3 pCi/g) was found only in the ash sample collected from the Yatağan coal fired power plant. An ash sample taken from the electro-filter of the Ambarli, a fuel oil fired-power plant of Turkey, was also analysed for comparision and found that it contained least amount of U-238.
Keywords: FT-IR Spectra; Coal ashes; EDXRF; γ-isotopic analysis